Crude Oil Prices, Household Spending and Economic Growth in the ASEAN-4 Region: An Analysis of Nonlinear Panel Autoregressive Distributed Lag - Rumbia, Wali Aya; Muthalib, Abd Azis; Abbas, Bakhtiar; Adam, Pasrun; Millia, Heppi; Saidi, La Ode; Azis, Muh. Irfandy (International Journal of Energy Economics and Policy, 2020)
This paper looks at the long run and short run asymmetric impact of crude oil prices on Indonesia’s economic growth. It also assesses whether household spending affects the economic growth in the ASEAN-4 Region (Indonesia, Singapore, Thailand and the Philippines) in the long run and short run. We use, to this end, annual time series data of crude oil prices, household consumption expenditure, and GDP for the period 1967-2018. To analyze the data, we employ a nonlinear panel autoregressive distributed lag model. The test results provide evidence that in the long-run, crude oil prices have an asymmetric impact on economic growth. Every 1% increase in crude oil prices, economic growth rises by 0.42%. Meanwhile, household spending does not affect economic growth in the long-run. Furthermore, in the short run, the test results show the presence of an asymmetric impact of crude oil prices on economic growth. Similarly, in the short run, household spending affects economic growth. Keywords: Crude Oil Prices, Household Spending, Economic Growth, Nonlinear Panel Autoregressive Distributed Lag Model. JEL Classifications: C33, E210, E310, O470. DOI: https://doi.org/10.32479/ijeep.9293